PENGARUH PERUSAHAAN KELUARGA, MULTINATIONAL COMPANY, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2012) - Nurul Hidayah; Kamaliah -; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research has a purpose to examine the influence of family company, multinational company and institutional ownership to tax avoidance. This study classified the type of research that is causative. The population in this study are all companies listed at the Indonesia Stock Exchange in 2010 until 2012. Sample used in this study was a 30 companies. The method using in the selection of sample by purposive sampling method. The data used in this research is a secondary data obtain from www.idx.co.id. The model of analysis used in this study is a program SPSS version 16.0 for Windows. The result of this research indicates that multinational company has a significant influence on tax avoidance activity. While the family ownership and institutional ownership have not significant influences on tax avoidance.Keywords: Tax Avoidance, Family Company, Multinational Company, and Institutional Ownership.